2011
DOI: 10.1007/s12024-010-9173-x
|View full text |Cite
|
Sign up to set email alerts
|

Age assessment by the Greulich and Pyle method compared to other skeletal X-ray and dental methods in data from Finnish child victims of the Southeast Asian Tsunami

Abstract: The validity of the age assessment method based on the "Radiographic Atlas of Skeletal Development of the Hand and Wrist" by Greulich and Pyle (1st edition 1950) has been frequently questioned. The purpose of this study was to examine the reliability of this widely used method and to compare it to various dental and other skeletal age assessment methods. Forty-seven Finnish children of known ages below 16 years, who perished in Thailand in the Southeast Asian Tsunami on 26 December 2004 were examined. Every vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 11 publications
4
13
0
Order By: Relevance
“…This method has been criticized, since the reference material was collected already in the 1930s and 1940s and is based on North American population [24,36]. The recent study of Varkkola and co-workers, where they examined the X-rays of the left wrist of the Finnish tsunami children victims, showed, however, that Greulich and Pyle atlas can be applied even today [42]. Moreover, the study of van Rijn et al from 2001 [43] confirmed its applicability in Dutch Caucasian children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been criticized, since the reference material was collected already in the 1930s and 1940s and is based on North American population [24,36]. The recent study of Varkkola and co-workers, where they examined the X-rays of the left wrist of the Finnish tsunami children victims, showed, however, that Greulich and Pyle atlas can be applied even today [42]. Moreover, the study of van Rijn et al from 2001 [43] confirmed its applicability in Dutch Caucasian children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, age estimation utilizing radiographs of the left-hand wrist and medial clavicles are recommended for use in forensic age estimation of the living (14,15). As a result, age estimation from analysis of the development of these two areas has come under increasing scrutiny (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Presently in the United Kingdom, there is an understandable reluctance to undertake radiographic imaging with the sole purpose of estimating age.…”
Section: Discussionmentioning
confidence: 99%
“…Dental development is less affected by environmental insults than is skeletal maturation and shows less variation between individuals than the development of the skeleton. For that reason, the use of dental development is more accurate for estimation of chronological age than the use of skeletal development .…”
Section: Resultsmentioning
confidence: 99%